Combined treatment and prevention strategies for hepatitis C virus elimination in the prisons in New South Wales: a modelling study. (12th November 2019) - Bretaña, Neil A.; Gray, Richard R.; Cunningham, Evan B.; Betz‐Stablein, Brigid; Ribeiro, Ruy; Graw, Frederik; Luciani, Fabio; Lloyd, Andrew R.
Abstract: Background and aims: Australia is currently on track to meet the World Health Organization (WHO) global hepatitis C virus (HCV) elimination goals by 2030, reflecting universal subsidized access to testing and direct‐acting antiviral (DAA) treatment. In New South Wales, DAA treatment in prisons has scaled‐up substantially, with 1000 prisoners treated in 2017. However, HCV prevalence and incidence in this setting is high, which could undermine elimination efforts. This study aimed to test the preventative effects of DAA treatment scale‐up, opiate substitution treatment (OST) and needle and syringe programme (NSP) strategies for prisons. Design: Modelling study using an individual‐based mathematical model of a typical prison setting. The model was calibrated against Australian epidemiological data sets and executed in‐prison events for each individual daily, including movements between prisons, changes in risk behaviour and uptake of prevention measures such as OST and NSP, as well as DAA treatment. Scenarios were projected from 2018 to 2030. Setting: New South Wales prisons. Participants: New South Wales prisoners. Measurements: Variables including prison populations, prevalence and incidence rate were calculated. Prisoners were described by demographic characteristics, HCV infection history, risk behaviours and accessing treatment and prevention measures in varied security settings. Findings: Increasing the number of prisoners treated for HCV to 2000 annually was projected to reduce the HCV incidence rate to 8.69 [95% confidence interval (CI) = 8.17, 9.20] per 100 person‐years (100 p.y.). Combined treatment and prevention strategies were necessary to reduce the projected incidence rate to 5.22 (95% CI = 5.13, 5.52) per 100 p.y. Considering the expected reductions in the prevalence of chronic HCV in the Australian community, incidence rate was predicted to drop to 0.93 (95% CI = 0.92, 0.98) per 100 p.y. by 2030. Conclusions: This model, which simulates prison scenarios to inform Australia's national hepatitis C virus elimination efforts, suggests that continued direct‐acting antiviral (coverage in the community combined with a moderate increase of direct‐acting antiviral treatments in prisons, and introduction of improved harm reduction via opiate substitution treatment and/or needle and syringe programmes, makes hepatitis C virus elimination feasible in Australian prisons.